How the Financial Crisis Has Affected the Economic Indicators of the Netherlands - Razvan Hagima (CES Working Papers, 2013)
Despite of being affected by the economic crisis, the Netherlands managed to minimize its effects. This situation is highlighted in a comparison with Romania and the European Union, between the levels of the most important economic indicators. Moreover, when other countries registered negative trends in their economic growth, the Dutch economy succeeded in this matter.
Keywords: G01; E00; 330; economic crisis; GDP growth rate; unemployment rate; budget deficit/surplus; inflation rate; FDI; foreign trade Romania